El liderazgo: un poder relativo - Huaylupo Alcázar, Juan (2022)
This article analyzes the epistemological, theoretical and historical implicit of the conception and practice of the leadership, in the public and also in the private administration. The mainly individualistic interpretation of the leadership is associated with peculiar forms of the interpretation of the history and the society, as well as, the conservation and reproduction of the power in the organizations, the society and the State. The leadership is a social relationship that expresses and represents the feelings and the aspirations of specific collectives, at all eradicated of becoming of the organization, neither of the social and historical contexts of the societies.